Scanning capacitance microscopy and related technologies for semiconductor device characterizations - Jiang, Yaoyao (2008)
This work reports on applying scanning capacitance microscopy (SCM), one relatively new technology to silicon device characterization. As an extension of scanning probe microscopy (SPM), scanning capacitance microscopy (SCM) has the unique ability to map high-resolution two-dimensional dopant profile of semiconductor device.